Wine & status: sociocultural dynamics of wine consumption from the perspective of Global History - Ferri, Gil Karlos; Sueli Nodari, Eunice (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article discusses the historical aspects of global wine consumption and the notion of status and social distinction. The analysis is presented through the field of Global History, using bibliographical review and related sources to weave a critical and current narrative on the topic. Wine consumption is intrinsically related to historical-geographical and sociocultural factors, revealing processes intertwined with asymmetrical power relations, class hierarchy, economic and cultural capital, predilections and exclusions. The appreciation of certain lifestyles – such as, in this case, the conspicuous consumption of wine – is a subjective social phenomenon increasingly constructed through advertising and in-person and virtual networks, subject to continuous change. The analysis of the historical trajectory of wine consumption as a symbol of social status represents an interesting opportunity to overcome a conventional and colonialist “wine world” and inserts historians in the current debate for a more sustainable and responsible wine industry with wine workers, the environment of the producing regions and respect for the health of the final consumer.